2018
DOI: 10.15557/jou.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonography in the diagnosis of occult scaphoid fractures

Abstract: Background: Ultrasonography is widely utilized by emergency physicians and radiologists to diagnose various orthopaedic diseases, including fractures. We aim to derive a definitive estimate of the diagnostic accuracy of ultrasonography in clinically suspected scaphoid fractures. Methods: We undertook a systematic review and meta-analysis of included diagnostic cohort studies that discussed the use of ultrasonography in the diagnosis of occult scaphoid fractures. We searched th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(36 reference statements)
0
11
0
1
Order By: Relevance
“…Moreover, physicians must keep in mind that BS is more invasive than the other modalities. Previous reviews by Kwee et al and Ali et al concluded that US can diagnose occult scaphoid fracture with a fairly high degree of accuracy and Kwee et al stated that US may be used when CT and MRI are not readily available [37,38]. Nonetheless, one needs to keep in mind that, although scaphoid fractures are the most frequently injured carpal bones, the consequences of fractures of other carpal bones should not be underestimated.…”
Section: Diagnostic Accuracy Of Imaging Of Carpal Fracturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, physicians must keep in mind that BS is more invasive than the other modalities. Previous reviews by Kwee et al and Ali et al concluded that US can diagnose occult scaphoid fracture with a fairly high degree of accuracy and Kwee et al stated that US may be used when CT and MRI are not readily available [37,38]. Nonetheless, one needs to keep in mind that, although scaphoid fractures are the most frequently injured carpal bones, the consequences of fractures of other carpal bones should not be underestimated.…”
Section: Diagnostic Accuracy Of Imaging Of Carpal Fracturesmentioning
confidence: 99%
“…Nonetheless, one needs to keep in mind that, although scaphoid fractures are the most frequently injured carpal bones, the consequences of fractures of other carpal bones should not be underestimated. All previously available systematic reviews only examined diagnostic tests for scaphoid fractures [32][33][34][35][36][37][38][39], while in practice it is often not quite clear during the diagnostic process which hand or wrist anatomical structure or tissue (soft tissue or bone) is affected.…”
Section: Diagnostic Accuracy Of Imaging Of Carpal Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Um eine Sensitivität von jeweils 86 und 89 % sowie eine Spezifität von 84-90 % anhand der vorhandenen Literatur berechnen [23,24].…”
Section: Magnetresonanztomographie (Mrt)unclassified